Service Section Design of the EDEN ISS Project - Vrakking, Vincent; Bamsey, Matthew; Zeidler, Conrad; Zabel, Paul; Schubert, Daniel; Romberg, Oliver (2017)
The international EDEN ISS project aims to investigate and validate techniques for plant cultivation in future bioregenerative life support systems. To this end the EDEN ISS project partners aim to design and build the Mobile Test Facility, which consists of two modified 20 foot shipping containers. One of these shipping containers is designated the Service Section and houses the bulk of the subsystem components, such as the Air Management System and Nutrient Delivery System, as well as a rack-sized plant cultivation system, which uses a standard International Space Station payload form factor. The subsystems within the Service Section ensure that the approximately 12.5 m² of cultivation area in the second container, the Future Exploration Greenhouse, have the proper environmental conditions, nutrients and illumination for optimal crop growth. The EDEN ISS project concluded its main design phase with a Critical Design Review in March 2016, thereafter proceeded into the hardware development and procurement phase of the project. This paper describes the final design of the Service Section at the start of the assembly, integration and testing phase, which will run until the complete Mobile Test Facility is shipped to Antarctica, where it arrives in December 2017, for a 12 month space analogue mission.